The Dangers of Carbon-Centric Conservation for Biodiversity: A Case Study in the Andes. (June 2014) - Duque, Alvaro; Feeley, Kenneth J.; Cabrera, Edersson; Callejas, Ricardo; Idarraga, Alvaro
Carbon-centric conservation strategies such as the United Nation's program to Reduce CO2 Emissions from Deforestation and Degradation (REDD+), are expected to simultaneously reduce net global CO2 emissions and mitigate species extinctions in regions with high endemism and diversity, such as the Tropical Andes Biodiversity Hotspot. Using data from the northern Andes, we show, however, that carbon-focused conservation strategies may potentially lead to increased risks of species extinctions if there is displacement (i.e., "leakage") of land-use changes from forests with large aboveground biomass stocks but relatively poor species richness and low levels of endemism, to forests with lower biomass stocks but higher species richness and endemism, as are found in the Andean highlands (especially low-biomass non-tree growth forms such as herbs and epiphytes that are often overlooked in biological inventories). We conclude that despite the considerable potential benefits of REDD+ and other carbon-centric conservation strategies, there is still a need to develop mechanisms to safeguard against possible negative effects on biodiversity in situations where carbon stocks do not covary positively with species diversity and endemism.